2007
DOI: 10.1088/0022-3727/40/8/015
|View full text |Cite
|
Sign up to set email alerts
|

Electro-thermal modelling of anode and cathode in micro-EDM

Abstract: Micro-electrical discharge machining is an evolution of conventional EDM used for fabricating three-dimensional complex micro-components and microstructure with high precision capabilities. However, due to the stochastic nature of the process, it has not been fully understood. This paper proposes an analytical model based on electro-thermal theory to estimate the geometrical dimensions of micro-crater. The model incorporates voltage, current and pulse-on-time during material removal to predict the temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
99
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(102 citation statements)
references
References 15 publications
0
99
0
1
Order By: Relevance
“…In other study, Hashimoto et al [10] reported a distribution of 34% and 48% discharge energy into the cathode and anode, respectively. Having modeled of heat distribution in anode and cathode in micro-EDM, Yeo et al [11] proposed a fraction of 14% and 39% of discharge energy to the anode and cathode, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In other study, Hashimoto et al [10] reported a distribution of 34% and 48% discharge energy into the cathode and anode, respectively. Having modeled of heat distribution in anode and cathode in micro-EDM, Yeo et al [11] proposed a fraction of 14% and 39% of discharge energy to the anode and cathode, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The discharge voltage Vd [11] at the onset of breakdown is: (2) where, α is a correction factor associated with dielectric strength, S is a constant based on electric field, n is a constant depending on the polarity, d is the inter-electrode gap length, A is the area of the tool electrode exposed to electric field and t is the time of breakdown. Furthermore, because of movement of electrons, the kinetic energy is converted into heat energy developed at the anode surface [12]. The heat flux q (r) at a radial coordinate r is given by:…”
Section: Electrical and Non-electrical Parameters In µEdmmentioning
confidence: 99%
“…When selecting the proper material for electrodes, one has to take into account not only conductivity, which is essential for electrodes in EDM, but also other features, like machinability and availability of the material along with thermal properties, mainly because of the thermal character of the process [24,25].…”
Section: Introductionmentioning
confidence: 99%